Prevalence and Management of Post-harvest Rots of Apple in Himachal Pradesh - Kumari, Neelam; Sharma, J. N. (International Journal of Economic Plants, 2024)
During a survey of post-harvest diseases of apple in Himachal Pradesh conducted during July to September 2021, fourteen different types of rots were observed. Among these, Penicillium expansum (blue mould) was most destructive with exclusive incidence of 43.8%. Surveys of different markets/stores of Himachal Pradesh revealed that the total losses due to apple decay at various locations varied from 7.80 to 21.93%. Ten important commercial varieties of apple were screened for their comparative susceptibility against fruit decay.Tydeman’s Early Worcester was found to be most tolerant to all the rot causing fungi with mean per cent rotting of 23.26%.Cow urine was found most effective in providing 79.21% growth inhibition of test fungi under study. The next best bio-products were Emblica officinalis (amla), Melia azadirach (darek) and Dodonaea viscose (mehandu) with per cent growth inhibition of 75.66, 73.59 and 68.48%, respectively. Under in vitro conditions, mancozeb (0.1%) was the most effective fungicide providing 84.83% growth inhibition. The efficacy of mancozeb as dip treatment at 0.1% concentration was judged to be significantly superior followed by 0.05% carbendazim with per cent control of 95.97 and 92.35%, respectively. Preharvest spray of mancozeb (0.3%) was highly effective in checking all the test fungi under different type of storage for 2 months. 1-methyl cyclopropene (MCP) fumigation of apple fruits immediately after harvesting for 12 hours was most effective in checking the test fungi under study providing 89.60% control.